The impact of climatic changes on forming the corn productivity in the western forest-steppe of Ukraine - A. Polevoy; T. Kostiukievych; А. Tolmachova; О. Zhygailo (Вісник аграрної науки Причорномор'я, 2021)
Currently, the trend of actively accelerating the pace of global warming has a negative impact on the current situation in the field of agriculture in many parts of the globe. According to current forecasts, the consequences caused by it will continue to intensify in the coming years. Many facts testify to the predominance of the negative consequences of these influences, including: an increase in temperature regimes, an increase in their variability, an increase in the amount and frequency of precipitation, an increase in periods of drought, and the presence of extreme weather phenomena. In addition, climate changes, increased humidity and CO2 in the air are making adjustments to crop yields. The main fodder crop in the world is corn, therefore adaptation of agricultural conditions to climatic fluctuations becomes an urgent stage for farmers. Today, corn meets demand not only in the food industry, but also in medicine and energy supply. The purpose of the work is to determine changes in the number of growing seasons and interphase periods of corn, to assess the photosynthetic productivity of crops and to forecast yield indicators. During the research, the method of comparison, monitoring, as well as observation and empirical research was used. The scenario of possible climate changes RCP 6.0 for the period until 2050 was used. The dynamic model of crop productivity, developed by A.M. Polovyi, was used as a research tool. The article presents the results of assessing the impact of climate change on the formation of corn productivity in the Western Forest Steppe of Ukraine. The value of the obtained results lies in their application in the development and improvement of the corn cultivation model in view of the widest list of climatic deviations